(untitled) (Research in Agriculture Livestock and Fisheries, 2019)
Ponds are considered to be self-contained, land lock ecosystem which is often teeming with rich vegetation and diverse organismal life. The pond water contains different organic and inorganic components. The experiment was carried out in laboratory, Department of Agricultural Chemistry, Bangladesh Agricultural University, Mymensingh through collection of pond water from Gouripur and Muktagacha under Mymensingh division for assessment of major ionic status and suitability parameters for irrigation and aquaculture usage in quantitative way. Around 30 samples were collected from different location. On the basis of HCO3 ion, all water samples except 3 samples were not suitable for irrigation because this anion exceeded the acceptable limit (1.5 meL-1). On the other hand, HCO3 ion was not treated as problematic in all samples except 2 samples for aquaculture usages. The concentrations of Ca, Mg, Na, K, PO4 and SO4 were far below the recommended limit. Considering aquaculture usage, Cl ion was considered as hazardous in all the pond water samples because this anion was above the legal limit (<0.003mgL-1). pH value of pond ranged from 7.02 to 7.87 indicating alkaline in nature and were not problematic for irrigation and aquaculture usage. Among the major ionic constituents, the remarkable significant correlations existed between Ca vs Mg, Ca vs K, Mg vs SO4, K vs Na, Na vs SO4. Res. Agric., Livest. Fish.6(2): 301-313, August 2019